EP219 Improvement in quality of life of Indian breast cancer patients by pre and post mastectomy educational counselling. (1st November 2019) - Mishra, A; Gowda, M; Deo, S
Abstract : Introduction/Background: In India still more than 70% of breast cancer patients are presenting in locally advanced stages, leading them to mastectomies. Being diagnosed as breast cancer patient and further undergoing radical surgery causing them a significat trauma and affecting their quality of life particularly in tems of body disfigurement, self -esteem, Social & personal relationship etc. Recognizing these issues, our aim was to assess the impact of educational counselling over quality of life of women who has undergone breast cancer mastectomy. Methodology: This is a prospective interventional study performed on breast cancer patients who have been treated at IRCH, AIIMS, New Delhi, India. Recruitment of 100 patients and data collection were done between Jan and Dec of 2017. All patients had undergone pre designed questionnaire based assessment of their knowledge regarding breast cancer. Out of 100, 50 patients randomly selected for 20 minutes pre & post mastectomy (POD-1) counselling sessions. After 12 months of mastectomy, all 100 patients again undergone a questionnaire based assessment regarding their quality of life. Statistical assessment done by Stuart Maxwell test & McNamara test. Results: Mean age of patients was 46.4 years. Almost 60% patients had finished their high school, 94% patients were married while only 15% were working. Out of 50 counselled patients 84.6% patients completed their treatment well and returned to their previous routine life while only 67.3% of un-counselled patients. Main issues addressed by patients were disfigurement, hair loss, loss of sensation and pain in operated side upper arm. Prior knowledge and motivtaion for the use of prosthetic bra, wigs, physiotherapy etc help them to return their normal life early. Conclusion: The short educational counselling sessions have a significant impact in the improvement of quality of life particularly in terms of emotional, physical and social life. Disclosure: Nothing to disclose.